Pregnancy-related Complications in Relation with Delivery Complication in Urban Public Health Center in 2019-2020: an Analytic Comparative Study - Abiyyu Didar Haq; Cut Warnaini; Muhammad Rizkinov Jumsa; Deasy Irawati (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2023)
Introduction: With a huge gap of knowledge and understanding created by the current pandemic, especially regarding maternal health, this research aimed to compare and analyze the correlation between pregnancy-related complications and delivery complications in an urban public health center before and during the pandemic. Methods:This is an analytic comparative study utilizing a retrospective cohort approach. Medical records of pregnant women during 2019-2020 were obtained from Pagesangan public health center with approved ethics from Mataram University and related government agencies. Collected data were then analyzed for each year and then compared between 2019 and 2020 to see if there were any significant differences between maternal health before and during the COVID-19 pandemic. Results: Medical records of 653 pregnant women were collected in this study. Twenty-two of 311 and 27 of 342 pregnancyrelated complications were recorded in 2019 and 2020, respectively. In contrast, 68 of 311 and 70 of 342 delivery complications were recorded in 2019 and 2020, respectively. Analysis was done to obtain each year’s relative risk (RR), and then we compared the obtained RR of both years. In 2019, the RR of pregnancy-related complications to delivery complications was 0,398 (95% CI 0,104-1,518); in 2020, the obtained RR was 0,522 (95% CI 0,176-1,550). Conclusion: Pregnancy-related complications were not the risk factor for delivery complications in both years. However, a significant correlation was found between maternal age and pregnancy-related complications in 2020, while in 2019, gravidity was also significantly related to delivery complications.